RELATIONSHIP OF POWER OF MC AND ADVERTISING COMMUNITY IN INCREASING BRANDING AT HOTEL BATU KARANG RESORT LEMBONGAN NUSA PENIDA BAL - Edy Mulyana, I Ketut (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Power Relations of Marketing Communication and Advertising Community. Advertising is one of the main commodities that becomes a bridge for producers to colonize and control the mindset of consumers. Various ways are taken by manufacturers so that their products sell well in the market. Starting from using famous actresses in advertisements, to giving promises that their products are the best and quality products. This research uses a qualitative approach with Fairclough's critical discourse analysis model. This type of research is observational research. The method used in this research is descriptive. The data in the text of this study are in the form of hotel advertisement images obtained from elections on the Batu Karang Instagram media. The research instrument is the researcher himself and the data collection technique is done by giving questionnaires to 15 managers in different areas at the Batu Karang Hotel. The results of this study found that (1) Advertising is one of the tools used by producers in offering their products, so that information about the product will arrive quickly and be easily remembered by consumers. (2) With the advertisement submitted on Instagram, it greatly affects the Branding of Hotel Batu Karang so that Hotel Batu Karang becomes more widely known both nationally and internationally. Hotel Batu Karang continues to actively advertise with various advertising methods to be able to make its products sell well in the market